A modified flavonoid accelerates oligodendrocyte maturation and functional remyelination. Issue 2 (6th September 2019) - Su, Weiping; Matsumoto, Steven; Banine, Fatima; Srivastava, Taasin; Dean, Justin; Foster, Scott; Pham, Peter; Hammond, Brian; Peters, Alec; Girish, Kesturu S.; Rangappa, Kanchugarakoppal S.; Basappa,; et al.
Abstract: Myelination delay and remyelination failure following insults to the central nervous system (CNS) impede axonal conduction and lead to motor, sensory and cognitive impairments. Both myelination and remyelination are often inhibited or delayed due to the failure of oligodendrocyte progenitor cells (OPCs) to mature into myelinating oligodendrocytes (OLs). Digestion products of the glycosaminoglycan hyaluronan (HA) have been implicated in blocking OPC maturation, but how these digestion products are generated is unclear. We tested the possibility that hyaluronidase activity is directly linked to the inhibition of OPC maturation by developing a novel modified flavonoid that functions as a hyaluronidase inhibitor. This compound, called S3, blocks some but not all hyaluronidases and only inhibits matrix metalloproteinase activity at high concentrations. We find that S3 reverses HA‐mediated inhibition of OPC maturation in vitro, an effect that can be overcome by excess recombinant hyaluronidase. Furthermore, we find that hyaluronidase inhibition by S3 accelerates OPC maturation in an in vitro model of perinatal white matter injury. Finally, blocking hyaluronidase activity with S3 promotes functional remyelination in mice with lysolecithin‐induced demyelinating corpus callosum lesions. All together, these findings support the notion that hyaluronidase activity originating from OPCs in CNS lesions is sufficient to prevent OPC maturation, which delays myelination or blocks remyelination. These data also indicate that modified flavonoids can act as selective inhibitors of hyaluronidase activity and can promote OPC maturation, making them excellent candidates to accelerate myelination or promote remyelination following perinatal and adult CNS insults. Main points: Modified flavonoids are selective hyaluronidase inhibitors. Hyaluronidases expressed by oligodendrocyte progenitors (OPCs) generate hyaluronan digestion products that inhibit OPC maturation. Blocking hyaluronidase activity accelerates remyelination.